Temperature oscillation of a dual compensation chamber loop heat pipe under acceleration conditions. (5th November 2021) - Lv, Xiaochen; Xie, Yongqi; Zhang, Hongxing; Xu, Yanmeng; Wu, Hongwei; Day, Rodney; Ren, Jianwei
Highlights: Temperature oscillation of DCCLHP is studied experimentally in acceleration field. Two loading modes on heat load and acceleration force are considered. Impacts of different acceleration magnitudes and directions are discussed. Physical mechanism of temperature oscillation in acceleration field is analyzed. Abstract: Loop heat pipe has a wide application in the fields of airborne electronics cooling and thermal management. However, the pertinent temperature oscillation of the loop heat pipe could lead to adverse effects on the electronics. In the current study, an ammonia-stainless steel dual compensation chamber loop heat pipe was developed to experimentally investigate the temperature oscillation under different acceleration conditions. The impact of several control parameters such as different heat loads, loading modes, acceleration directions and magnitudes on the operational performance of the loop heat pipe was analyzed in a systematic manner. The heat load applied on the evaporator ranged from 25 W to 300 W. The acceleration magnitude varied from 1 g to 9 g and four different acceleration direction, i.e. configurations A, B, C and D, were taken into account. Two different loading modes were applied with different heat load and acceleration force. Experimental results show that (i) the loop temperature will change and oscillate as the acceleration force was applied under all test conditions. It can be easily found that the temperature oscillation occurred at both heat loads of 250 W and 300 W. (ii) for the case of the first loading mode, periodic temperature oscillation is observed on the liquid line, whereas for the second loading mode, periodic temperature oscillation can be easily appeared on the entire loop. (iii) the loop temperature under both configurations A and B with acceleration of 7 g does not oscillate at heat load of 150 W, 200 W and 250 W when the first loading mode is applied. Especially under configuration B, the acceleration could contribute to repress the temperature oscillation. Under the current heat loads for almost all cases, the temperature oscillation can be observed for configurations A, C and D with acceleration of 5 g. (iv) the amplitude of evaporator at heat load of 300 W under configuration C are 0.6 °C, 0.3 °C, 0.2 °C and 0.3 °C with acceleration of 3 g, 5 g, 7 g and 9 g. The corresponding period is 66 s, 36 s, 34 s and 36 s, respectively.